Playgroups as sites for parental education. (September 2017) - McLean, Karen; Edwards, Susan; Evangelou, Maria; Skouteris, Helen; Harrison, Linda J; Hemphill, Sheryl A; Sullivan, Peter; Lambert, Pamela
There is widespread international interest in parental education as a means of promoting educational equality through improving educational outcomes for young children. The research in this area suggests an association between the home learning environment and children's educational outcomes and highlights the importance of parental education for supporting young children's learning through play. This article reviews the international literature around parental education initiatives (or 'interventions') in early childhood and then considers playgroups as potential sites for parental education. The article identifies the universal features of playgroups that make these sites appealing for the implementation of parental education initiatives and discusses the complexities associated with the design of interventions aimed at meeting the diverse needs of parents attending playgroups. It concludes by providing a case for community playgroups as cultural contexts, to be considered sites for parental education through curriculum aimed at supporting parents to actively engage in their children's learning and development through play.